La radio comme vecteur d’identité culturelle: le cas de la politique canadienne de radiodiffusion - Jullion, Marie-Christine; Cennamo, Ilaria (Ponti/Ponts, 2021)
This contribution aims at highlighting the cultural role played by the radio in Canada, as set out by the Canadian broadcasting policy. Cultural identity is a very complex phenomenon, which can be analysed from different perspectives: historical, anthropological and psychological, for instance. According to the discursive perspective, identity and cultural items can be observed through the analysis of discursive formulation and argumentation, as well as the identification of terminological, lexical and stylistic choices. On the basis of the analysis of the fundamental principles set out by the Canadian broadcasting Act (1991), as well as the integration of a selection of documents published by the CRTC (Canadian Radio-television and Telecommunications Commission) on its official website, this study will be focused on the observation of those discursive elements which have been deployed in order to define the radio as a Canadian cultural project. This analysis will be completed by the identification of some cultural and linguistic items, which shows that the above-mentioned principles established by the Canadian broadcasting policy have been taken into account with respect to the elaboration of Canadian programming content offered by Radio-Canada. In conclusion, some research questions will be raised in order to suggest new avenues for the study of the cultural and political role played by the radio in the present (and future) context of globalization, in the light of modern technological developments.